A Novel Hypovirus Species From Xylariaceae Fungi Infecting Avocado - Velasco, Leonardo; Arjona-Girona, Isabel; Ariza-Fernández, María T.; Cretazzo, Enrico; López-Herrera, Carlos (Frontiers in Microbiology, 2018)
The white rot root disease caused by Rosellinia necatrix is a major concern for avocado cultivation in Spain. Healthy escapes of avocado trees surrounded by diseased trees prompted us to hypothesize the presence of hypovirulent R. necatrix due to mycovirus infections. Recently, we reported the presence of another fungal species, Entoleuca sp., belonging to the Xylariaceae, that was also found in healthy avocado trees and frequently co-infecting the same roots than R. necatrix. We investigated the presence of mycoviruses that might explain the hypovirulence. For that, we performed deep sequencing of dsRNAs from two isolates of Entoleuca sp. that revealed the simultaneous infection of several mycoviruses, not described previously. In this work, we report a new member of the Hypoviridae, tentatively named Entoleuca hypovirus 1 (EnHV1). The complete genome sequence was obtained for two EnHV1 strains, which lengths resulted to be 14,958 and 14,984 nt, respectively, excluding the poly(A) tails. The genome shows two ORFs separated by a 32-nt inter-ORF, and both 5′- and 3′-UTRs longer than any other hypovirus reported to date. The analysis of virus-derived siRNA populations obtained from Entoleuca sp. demonstrated antiviral silencing activity in this fungus. We screened a collection of Entoleuca sp. and R. necatrix isolates and found that EnHV1 was present in both fungal species. A genetic population analysis of EnHV1 strains revealed the presence of two main clades, each of them including members from both Entoleuca sp. and R. necatrix, which suggests intra- and interspecific virus transmission in the field. Several attempts failed to cure Entoleuca sp. from EnHV1. However, all Entoleuca sp. isolates collected from avocado, whether harboring the virus or not, showed hypovirulence. Conversely, all R. necatrix isolates were pathogenic to that crop, regardless of being infected by EnHV1.